Knowledge management action plan 2021-2025 knowledge for a prosperous, inclusive, resilient, and sustainable Asia and Pacific. - Lim, Genevieve
The KMAP strengthens ADB ability to better deliver tailored knowledge solutions, together with financing, to developing member countries. It emphasizes increasing collaboration, improving the quality and efficiency of knowledge services, making knowledge work more attractive, and using a country focused approach all of which contribute to ADB value addition, boost client satisfaction, and bolster ADB role as a trusted knowledge provider.